The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.08.26.266726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of selective cell death in HIV-1-infected cells by DDX3 inhibitors leads to depletion of the inducible reservoir

Abstract: An innovative approach to eliminate HIV-1-infected cells emerging out of latency, the major hurdle to HIV-1 cure, is to pharmacologically reactivate viral expression and concomitantly trigger intracellular pro-apoptotic pathways in order to selectively induce cell death (ICD) of infected cells, without reliance on the extracellular immune system. In this work we demonstrate the effect of DEAD-box polypeptide 3, X-Linked (DDX3) inhibitors on selectively inducing cell death in latent HIV-1-infected cell lines, p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…To analyze the dynamics of viral RNA (vRNA) and/or GFP-producing cells by FISH-Flow, five million control and PCID2-knockdown cells were collected, fixed, permeabilized and processed as described before 13 using the PrimeFlow RNA assay (ThermoFisher Scientific) according to manufacturer protocol. Viral RNA producing cells were detected by labelling HIV-1 unspliced mRNA with a set of 40 probe pairs against the GagPol region (Affymetrix eBioscience catalogue number GagPol HIV-1 VF10-10884) and RPL13A (Affymetrix eBioscience, catalogue number VA-13187) as a control diluted 1:5 in diluent provided in the kit and hybridized to the target HIV-1 vRNA for 2 hours at 40°C.…”
Section: Fish-flowmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the dynamics of viral RNA (vRNA) and/or GFP-producing cells by FISH-Flow, five million control and PCID2-knockdown cells were collected, fixed, permeabilized and processed as described before 13 using the PrimeFlow RNA assay (ThermoFisher Scientific) according to manufacturer protocol. Viral RNA producing cells were detected by labelling HIV-1 unspliced mRNA with a set of 40 probe pairs against the GagPol region (Affymetrix eBioscience catalogue number GagPol HIV-1 VF10-10884) and RPL13A (Affymetrix eBioscience, catalogue number VA-13187) as a control diluted 1:5 in diluent provided in the kit and hybridized to the target HIV-1 vRNA for 2 hours at 40°C.…”
Section: Fish-flowmentioning
confidence: 99%
“…Further blocks to HIV-1 gene expression occur at a posttranscriptional level, including inhibition of viral RNA (vRNA) splicing, nucleocytoplasmic export, translation and trafficking (reviewed in 4 ). The contribution of these RNA processing mechanisms to the overall repression of HIV-1 gene expression has recently been characterized in both in vitro models of HIV-1 latency and CD4+ T cells obtained from people living with HIV-1 (PLWH) [10][11][12][13][14] , where it has been shown that blocks to HIV-1 gene expression occur largely at post-transcriptional levels. More recently, several unbiased and candidate studies, including our own, have successfully identified co-and post-transcriptional regulators of HIV-1 latency that control vRNA metabolism and either promote or inhibit viral gene expression 12,15,16 .…”
Section: Introductionmentioning
confidence: 99%